2011
DOI: 10.1002/ajhb.21226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cortisol disproportionately impacts fetal growth in male offspring: Evidence from the philippines

Abstract: Objectives Lower birth weight (BW) re-occurs across generations, but the intermediate mechanisms remain poorly understood. One potential pathway involves cortisol, which may be elevated in women born small and in turn could lead to fetal growth restriction in offspring. To test this possibility, we evaluated whether BW predicts hypothalamic-pituitary-adrenal (HPA) function in the non-pregnant state in a cohort of young Filipino women, and whether differences in HPA function predict offspring BW. Methods Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 15 publications
3
38
1
Order By: Relevance
“…In addition, women with higher evening cortisol are more likely to experience adverse birth outcomes, such as reduced fetal growth (Goedhart et al, 2010;Thayer et al, 2012) and shorter length of gestation (Sandman et al, 2006). Notably, the relationship we report between perceived discrimination and evening cortisol remained after controlling for material deprivation, suggesting that these effects are independent of socioeconomic status in our sample.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…In addition, women with higher evening cortisol are more likely to experience adverse birth outcomes, such as reduced fetal growth (Goedhart et al, 2010;Thayer et al, 2012) and shorter length of gestation (Sandman et al, 2006). Notably, the relationship we report between perceived discrimination and evening cortisol remained after controlling for material deprivation, suggesting that these effects are independent of socioeconomic status in our sample.…”
Section: Discussioncontrasting
confidence: 36%
“…These findings suggest that the experience of discrimination may not only impact risk for developing chronic disease in the present generation, but also in future generations (Goosby and Heidbrink, 2013;Kuzawa and Sweet, 2009;Wells, 2010). In support of this hypothesis, both elevated maternal cortisol outside of pregnancy, and ethnic discrimination experience, have been independently associated with the development of smaller birth size (Collins et al, 2000;Thayer et al, 2012). However, no study has evaluated whether the normal increase in cortisol during gestation (Wadhwa, 2005) is further elevated in response to discrimination experience.…”
Section: Introductionmentioning
confidence: 69%
“…Despite the lack of correlation between maternal and offspring hair GCs, we found that infant hair GCs positively predicted neonatal body size. This pattern runs counter to observational studies on humans (Thayer et al, ; Field et al, ), as well as experimental research investigating the influence of synthetic GCs on neonatal body mass (Jobe et al, ). Although results from such studies likely reflect extreme types of physiological stress (associated with modern human lifestyles or captive environments), experimental studies are particularly problematic because synthetic GCs are often administered at exaggerated dosage levels and can pass unrestricted across the placenta.…”
Section: Discussionmentioning
confidence: 69%
“…Further, outside of humans (Field, Diego, & Hernandez‐Reif, ; Thayer, Feranil, & Kuzawa, ), some studies supporting the link between maternal GCs and fetal growth restriction have relied on exogenously administered synthetic GCs (e.g., dexamethasone, betamethasone), which frequently exceed naturally occurring levels of endogenous hormone and can pass across the placenta unobstructed (e.g., Jobe, Newnham, Willet, Sly, & Ikegami, ; reviewed in Seckl, ). Thus, the growth effects established by these studies may exaggerate the role of endogenous maternal cortisol on neonatal body mass among typical gestations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the biological mechanisms underlying the life-history hypotheses are uncertain: how do high rates of mortality or, rather, the prevalent causes of mortality, such as disease and nutritional stress, induce earlier reproductive maturity in some but not all (see Hill and Hurtado 1996) populations of hunter-gatherers? A plausible but underexplored mechanism stems from the emerging field of human immunological ecology (McDade 2003(McDade , 2005 and the concept of inflammation "memory" across the life cycle and in subsequent generations (McDade et al 2011;Thayer and Kuzawa 2011;Kuzawa et al 2012;Thayer et al 2012;Tallman et al 2012). Here we explore and attempt to test this epigenetic premise.…”
mentioning
confidence: 99%